The magic in changing your stars - Henderson, Leah (Sterling Children's Books, 2020)
After bungling his audition to play the Scarecrow in The Wiz, fifth-grader Ailey is magically transported to 1930s Harlem where he meets his own grandfather and legendary tap dancer Bill "Bojangles" Robinson.